TBLT Task and Framework: Insights from Indonesian Context - Sukma, Doris (Journal of English Language Teaching, Literature and Culture, 2024)
This study employs a document study to investigate the tasks and TBLT framework used in Indonesian English classrooms. Through a rigorous examination of existing literature and empirical research, this study will elucidate how these practices contribute to the development of communicative competence, a core tenet of the Merdeka Curriculum. Several recent studies (past five years) on TBLT practices have been identified through a review of open-access journals. The findings reveal a prevalence of authentic tasks, consistent with expert recommendations, but with varying levels of authenticity. In addition, implementing TBLT generally aligns with established principles, particularly those proposed by Willis, but only aÃ‚Â few adaptations are made to suit local teaching and learning goals. While these findings suggest a positive trend, further analysis is needed to identify potential areas for improvement and inform future TBLT practices in Indonesian classrooms.